Sodium-ion battery hard carbon material and electrode material prepared from sodium-ion battery hard carbon material
Through hydrothermal reaction of glucose and polycationic compounds and high-temperature pyrolysis carbonization treatment, hard carbon materials with high reversible capacity and high first-week Coulomb efficiency were prepared, which solved the problem of insufficient electrochemical performance of hard carbon materials and achieved environmentally friendly and economical industrial application.
Patent Information
- Application Number
- CN202510055759.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The electrochemical properties of hard carbon materials in the prior art still need to be improved.
Through the hydrothermal reaction of glucose and polycationic compounds, the electrostatic adsorption of hydroxyl groups on the surface of carbon spheres and polycationic compounds is formed. Combined with high-temperature pyrolysis carbonization, a stable hard carbon precursor is prepared to form a hard carbon material with high reversible capacity and high first-week Coulomb efficiency.
The prepared hard carbon material has high reversible capacity and high first-week Coulomb efficiency. It has a wide range of materials and is cheap. It is suitable for large-scale industrial production.
Smart Images

Figure CN119873784A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery hard carbon material and an electrode material prepared therefrom. Background Art
[0002] Sodium-ion batteries (SIBs) have similar mechanisms to lithium-ion batteries (LIBs) and may be cheaper. Compared with lithium-ion batteries, sodium is very abundant in the earth's crust, while relatively scarce lithium is concentrated in limited geological areas. Therefore, SIBs are becoming the grid-level energy storage technology closest to the market outside of LIB technology, and the development of lithium-ion batteries has provided rich experience for SIB development. At present, the performance of SIBs, including energy density, power density and cycle life, is almost comparable to that of commercial LIBs. Among them, hard carbon is the most advanced SIB anode material, because hard carbon, which is difficult to graphitize, has high reversible capacity and can be simply synthesized by controlled carbonization of low-cost carbon-rich polymer precursors. The synthesized hard carbon shows a disordered structure and strong cross-linking between graphene layers. However, the electrochemical performance of hard carbon materials in existing technologies still needs to be improved. Summary of the invention
[0003] The purpose of the present application is to provide a sodium ion battery hard carbon material and an electrode material prepared therefrom, so as to solve the problem that the electrochemical performance of the hard carbon materials in the prior art still needs to be improved.
[0004] To achieve the above object, the present application provides a sodium ion battery hard carbon material, and the preparation method of the sodium ion battery hard carbon material comprises the following steps:
[0005] Step 1: Dissolve glucose in deionized water and stir to dissolve to prepare a glucose solution;
[0006] Step 2, adding the polycationic compound to the glucose solution obtained in step 1 and stirring to make the two mixed evenly to obtain a mixed solution;
[0007] Step 3: transferring the mixed solution obtained in step 2 to a hydrothermal reactor for hydrothermal treatment. After the reaction is completed, the hydrothermal product is centrifuged, washed and dried;
[0008] Step 4: Transfer the hydrothermal product after the drying treatment in step 3 to a high-temperature tube furnace, and perform high-temperature pyrolysis and carbonization treatment under an inert atmosphere to obtain a hard carbon material.
[0009] Preferably, the concentration of the glucose solution is 50-80 g / L, the concentration of the polycationic compound solution is 2-5 g / L, and the polycationic compound is one or more of polyethyleneimine, polydiallyldimethylammonium chloride and polyacrylamide.
[0010] Preferably, the glucose solution is 60 g / L and the polycationic compound solution is 3 g / L.
[0011] Preferably, the hydrothermal reaction temperature of the mixed solution of glucose and polycationic compound is 160-200° C., and the hydrothermal reaction time is 12-24 h.
[0012] Preferably, the hydrothermal reaction temperature of the mixed solution of glucose and polycationic compound is 180° C., and the hydrothermal reaction time is 15 h.
[0013] Preferably, in step three, centrifugal washing is performed at least 3 times, the drying temperature is 80° C., and the drying time is 24 h.
[0014] Preferably, in step 4, the inert atmosphere of high-temperature pyrolysis carbonization includes nitrogen and argon, the high-temperature pyrolysis carbonization temperature is 1100-1500°C, the high-temperature pyrolysis carbonization heating rate is 2-8°C / min, and the high-temperature pyrolysis carbonization insulation time is 2-5h.
[0015] Preferably, in step 4, the high-temperature pyrolysis carbonization temperature is 1300° C., the high-temperature pyrolysis carbonization heating rate is 5° C. / min, and the high-temperature pyrolysis carbonization insulation time is 3 h.
[0016] The present application also provides a sodium ion battery hard carbon electrode material, comprising the above-mentioned sodium ion battery hard carbon material, the hard carbon material and the conductive agent acetylene black and the binder sodium carboxymethyl cellulose are ground into a uniform slurry according to a mass ratio of 8:1:1, and then coated on a copper foil by a coater, and cut into battery pole pieces with a diameter of 12 mm after drying at 60°C, and the active material mass is 1.2-2.0 g / cm 2 .
[0017] Therefore, the present application provides a sodium ion battery hard carbon material and its prepared electrode material, wherein glucose and a polycationic compound are treated by hydrothermal reaction, a large number of hydroxyl groups are formed on the surface of glucose during the hydrothermal polymerization process to form carbon balls, so that the surface of the carbon balls has a negative charge, and the polycationic compound forms a polycationic electrolyte in an aqueous solution, and electrostatic adsorption occurs with the negatively charged carbon balls, while the hydroxyl groups and amino groups on the long chain of the polycationic compound form hydrogen bonds and molecular crosslinking with the carbon balls, thereby preparing a hard carbon precursor with a stable structure, and then obtaining a hard carbon negative electrode material by high-temperature pyrolysis and carbonization. The hard carbon prepared by the invention has a high reversible capacity and a high first-cycle coulombic efficiency as a negative electrode material for sodium ion batteries, and has the following beneficial effects:
[0018] 1. The raw materials of the present invention are all biomass-based materials, which have the advantages of wide sources, low prices and green environmental protection. The method used is simple in preparation process, economically feasible and applicable, and has application prospects for large-scale industrial production.
[0019] 2. The present invention is based on the principle of molecular interaction, namely, intermolecular hydrogen bonding, intermolecular chemical cross-linking and electrostatic adsorption between compounds with different charges. The hard carbon material prepared by high-temperature pyrolysis and carbonization of the hard carbon precursor has excellent rate performance, with a reversible specific capacity of up to 315.18 mAh / g and a first-week coulombic efficiency of 92.91%. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM image of the hard carbon-based sodium ion battery negative electrode material based on molecular action prepared in Example 1;
[0021] Figure 2 The charge and discharge curves of the molecular action hard carbon-based sodium ion battery negative electrode material prepared in Example 1 at a current density of 0.05 A / g in the first three cycles;
[0022] Figure 3 This is a rate performance diagram of the hard carbon-based sodium ion battery negative electrode material based on molecular action prepared in Example 1 at a current density of 0.05A / g-1A / g;
[0023] Figure 4 This is the charge and discharge curve of the hard carbon-based sodium ion battery negative electrode material based on molecular action prepared in Example 1 at a current density of 0.05A / g-1A / g. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further illustrated by the following examples.
[0025] Example 1
[0026] (1) Dissolve 3.6 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0027] (2) Add 0.18 g of polyethyleneimine into the glucose solution and stir for 3 h to mix the two evenly.
[0028] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 180° C. for 15 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0029] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0030] Example 2
[0031] (1) Dissolve 3.6 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0032] (2) Add 0.18 g of polydiallyldimethylammonium chloride into the glucose solution and stir for 3 h to mix the two evenly.
[0033] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 180° C. for 15 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0034] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0035] Example 3
[0036] (1) Dissolve 3.6 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0037] (2) Add 0.18 g of polyacrylamide into the glucose solution and stir for 3 h to mix the two evenly.
[0038] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 180° C. for 15 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0039] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0040] Example 4
[0041] (1) Dissolve 3.6 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0042] (2) Add 0.18 g of polyethyleneimine into the glucose solution and stir for 3 h to mix the two evenly.
[0043] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 200° C. for 15 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0044] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0045] Example 5
[0046] (1) Dissolve 3.6 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0047] (2) Add 0.18 g of polyethyleneimine into the glucose solution and stir for 3 h to mix the two evenly.
[0048] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 160° C. for 15 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0049] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0050] Example 6
[0051] (1) Dissolve 3.6 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0052] (2) Add 0.18 g of polyethyleneimine into the glucose solution and stir for 3 h to mix the two evenly.
[0053] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 180° C. for 12 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0054] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0055] Example 7
[0056] (1) Dissolve 3.6 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0057] (2) Add 0.18 g of polyethyleneimine into the glucose solution and stir for 3 h to mix the two evenly.
[0058] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 180° C. for 24 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0059] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0060] Example 8
[0061] (1) Dissolve 3.6 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0062] (2) Add 0.18 g of polyethyleneimine into the glucose solution and stir for 3 h to mix the two evenly.
[0063] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 180° C. for 15 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0064] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1500° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0065] Example 9
[0066] (1) Dissolve 3.6 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0067] (2) Add 0.18 g of polyethyleneimine into the glucose solution and stir for 3 h to mix the two evenly.
[0068] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 180° C. for 15 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0069] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace, and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1100° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0070] Example 10
[0071] (1) Dissolve 3.6 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0072] (2) Add 0.12 g of polyethyleneimine into the glucose solution and stir for 3 h to mix the two evenly.
[0073] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 180° C. for 15 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0074] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0075] Embodiment 11
[0076] (1) Dissolve 3.6 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0077] (2) Add 0.24 g of polyethyleneimine into the glucose solution and stir for 3 h to mix the two evenly.
[0078] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 180° C. for 15 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0079] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min and kept at this temperature for 5 h to obtain a hard carbon negative electrode material.
[0080] Example 12
[0081] (1) Dissolve 3 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve it.
[0082] (2) Add 0.18 g of polyethyleneimine into the glucose solution and stir for 3 h to mix the two evenly.
[0083] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 180° C. for 15 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0084] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0085] Example 13
[0086] (1) Dissolve 4.8 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0087] (2) Add 0.18 g of polyethyleneimine into the glucose solution and stir for 3 h to mix the two evenly.
[0088] (3) The mixed solution was transferred to a hydrothermal reactor for hydrothermal treatment at a temperature of 180° C. for 15 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0089] (4) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0090] Comparative Example 1
[0091] (1) Dissolve 3.6 g of glucose in 60 mL of deionized water and stir for 1 h to fully dissolve.
[0092] (2) The glucose solution was transferred to a hydrothermal reactor for hydrothermal treatment. The hydrothermal reaction temperature was 180° C. and the hydrothermal reaction time was 15 h. After the reaction was completed and cooled to room temperature, the hydrothermal reaction product was centrifuged, washed and dried.
[0093] (3) The hydrothermal reaction product after the above treatment was transferred to a high-temperature tubular furnace and subjected to high-temperature pyrolysis and carbonization treatment in an argon atmosphere. The temperature was increased to 1300° C. at a heating rate of 5° C. / min and kept at this temperature for 3 h to obtain a hard carbon negative electrode material.
[0094] Application and performance testing
[0095] The finished hard carbon material prepared by the above-mentioned embodiments and comparative examples was ground into a uniform slurry with the conductive agent acetylene black and the binder sodium carboxymethyl cellulose in a mass ratio of 8:1:1, and then coated on a copper foil by a coating device, and then cut into battery pole pieces with a diameter of 12 mm after drying at 60°C, and used as the negative electrode active material of the sodium ion battery to prepare pole pieces (active material surface loading 1.2-2 mg / cm -2 ), and prepared sodium ion button batteries in a glove box, and tested the electrochemical properties of the button batteries.
[0096] Table 1 shows the battery performance of the negative electrode material of the hard carbon-based sodium ion battery based on molecular action. Compared with the comparative example, the embodiment has higher reversible capacity and first-week coulomb efficiency. This is because glucose forms carbon balls during the hydrothermal reaction process, and the surface of the carbon balls contains a large number of hydroxyl groups, which make the surface negatively charged, and have an electrostatic adsorption effect with the positively charged polycationic compound. The hydroxyl groups on the surface of the carbon balls form hydrogen bonds and molecular crosslinks with the groups of the polycationic compound, which, on the one hand, make the hard carbon precursor doped with nitrogen. On the other hand, the polycationic compound, as a long-chain macromolecule, can minimize the surface defects of the hard carbon (such as Figure 1 ). Promote Na + The rapid transfer of , makes it have excellent rate performance and good reversible specific capacity (as shown in Table 1 and Table 2), such as Figure 2 Example 1 still has a reversible capacity of 315 mAh / g at a current density of 0.05 A / g, the first cycle coulombic efficiency is as high as 92.9%, and the charge and discharge curves of the first three cycles are highly overlapped, indicating its good reversibility. Figure 2 and Figure 3 Example 1 shows excellent rate performance and has a high reversible capacity of 197 mAh / g even at a current density of 1.0 A / g, which proves the superiority of the hard carbon-based sodium ion battery negative electrode material based on molecular action of the present invention.
[0097] Table 1 Electrochemical performance of the examples and comparative examples (current density 0.05Ag -1 )
[0098] Example Discharge specific capacity (mAh / g) Charge capacity (mAh / g) First week coulomb efficiency (%) Example 1 339 315 92.9 Example 2 357 306 85.7 Example 3 320 289 90.3 Example 4 336 295 87.8 Example 5 342 301 88.0 Example 6 319 275 86.2 Example 7 323 289 89.5 Example 8 312 281 90.1 Example 9 283 196 69.3 Example 10 336 303 90.2 Embodiment 11 345 300 87.0 Example 12 311 280 90.0 Example 13 362 308 85.1 Comparative Example 1 289 212 73.4
[0099] Table 2 Electrochemical performance of Example 2 at different current densities (0.05-1.0 mA / g)
[0100] Current density (mA / g) 0.05 0.1 0.2 0.3 0.5 0.8 1.0 Discharge specific capacity (mAh / g) 339 311 296 281 259 225 200 Charge specific capacity (mAh / g) 315 304 289 276 252 220 197
[0101] Therefore, the present application provides a sodium ion battery hard carbon material and an electrode material prepared therefrom. Based on the interaction between hard carbon precursor molecules, glucose and polycationic compounds are cross-linked at the molecular level, and a hard carbon precursor is prepared by a hydrothermal reaction. On the one hand, the polycationic compound contains nitrogen elements, and the doping of heteroatoms can provide more sodium storage sites for hard carbon and increase the reversible capacity. On the other hand, it can improve the surface structure of hard carbon, increase electronic conductivity and interlayer spacing, etc., thereby improving the electrochemical properties of hard carbon negative electrode materials for sodium ion batteries.
[0102] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.
[0103] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A sodium ion battery hard carbon material, characterized in that: The preparation method of the hard carbon material for sodium ion battery comprises the following steps: Step 1: Dissolve glucose in deionized water and stir to dissolve to prepare a glucose solution; Step 2, adding the polycationic compound to the glucose solution obtained in step 1 and stirring to make the two mixed evenly to obtain a mixed solution; Step 3: transferring the mixed solution obtained in step 2 to a hydrothermal reactor for hydrothermal treatment. After the reaction is completed, the hydrothermal product is centrifuged, washed and dried; Step 4: Transfer the hydrothermal product after the drying treatment in step 3 to a high-temperature tube furnace, and perform high-temperature pyrolysis and carbonization treatment under an inert atmosphere to obtain a hard carbon material.
2. A sodium ion battery hard carbon material according to claim 1, characterized in that: The concentration of the glucose solution is 50-80 g / L, the concentration of the polycationic compound solution is 2-5 g / L, and the polycationic compound is one or more of polyethyleneimine, polydiallyldimethylammonium chloride and polyacrylamide.
3. A sodium ion battery hard carbon material according to claim 1, characterized in that: The glucose solution was 60 g / L, and the polycationic compound solution was 3 g / L.
4. A sodium ion battery hard carbon material according to claim 1, characterized in that: The hydrothermal reaction temperature of the mixed solution of glucose and polycationic compound is 160-200° C., and the hydrothermal reaction time is 12-24 hours.
5. A sodium ion battery hard carbon material according to claim 1, characterized in that: The hydrothermal reaction temperature of the mixed solution of glucose and polycationic compound is 180°C, and the hydrothermal reaction time is 15h.
6. A sodium ion battery hard carbon material according to claim 1, characterized in that: In step 3, centrifugal washing is performed at least 3 times, the drying temperature is 80° C., and the drying time is 24 h.
7. A sodium ion battery hard carbon material according to claim 1, characterized in that: In step 4, the inert atmosphere of high-temperature pyrolysis carbonization includes nitrogen and argon, the high-temperature pyrolysis carbonization temperature is 1100-1500° C., the high-temperature pyrolysis carbonization heating rate is 2-8° C. / min, and the high-temperature pyrolysis carbonization insulation time is 2-5h.
8. A sodium ion battery hard carbon material according to claim 1, characterized in that: In step 4, the high-temperature pyrolysis carbonization temperature is 1300° C., the high-temperature pyrolysis carbonization heating rate is 5° C. / min, and the high-temperature pyrolysis carbonization insulation time is 3 h.
9. A hard carbon electrode material for a sodium ion battery, characterized in that: The sodium ion battery hard carbon material comprises the hard carbon material according to any one of claims 1 to 8, wherein the hard carbon material, the conductive agent acetylene black, and the binder sodium carboxymethyl cellulose are ground into a uniform slurry according to a mass ratio of 8:1:1, and the slurry is applied on a copper foil by a coating device, and the slurry is dried at 60°C and cut into battery pole pieces with a diameter of 12 mm, and the mass of the active material is 1.2-2.0 g / cm 2 .
Citation Information
Patent Citations
Preparation method, product and application of nitrogen-doped hard carbon material
CN113644269A
Preparation method of biomass derived hard carbon negative electrode material and energy storage battery
CN117525396A
Sodium-ion battery hard carbon negative electrode material prepared by biomass-based crosslinking and application of sodium-ion battery hard carbon negative electrode material
CN117623270A
Sodium ion battery negative electrode material and preparation method thereof
CN117995997A
High-carbon-yield nitrogen-doped sodium ion battery hard carbon negative electrode material and preparation method thereof
CN118026145A
Cited By
Hard carbon negative electrode material synthesized by rhizopus through Maillard reaction and preparation method and application of hard carbon negative electrode material
CN120646811A